HEPATOCELLULAR CARCINOMA. RECENT ADVANCES IN DIAGNOSIS AND TREATMENT - T. Y. Chernobrovkina; Y. D. Yankovwskaya (Архивъ внутренней медицины)
In analytical review describes the pathogenic mechanisms of hepatocarcinogenesis and some risk factors of grow more serious progress of HCC. There modern classifications of HCC, aetiology, some of diagnostic methods in suspicion on HCC and different variants of treatment by means of medical drugs and nonmedical tactics are presented. The main risk factors for the development HCC — liver cirrhosis, man, the age of 50 year, HBV DNA > 104 copies/ml, positive HBeAg in blood serum, genotype С HBV, mutations in the area core promoter, increased activity ALT. The clinical example of patient with HCC and the outcome of liver cirrhosis are illustrated.